Body Appreciation, Depressive Symptoms, and Self-Esteem in Pregnant and Postpartum Brazilian Women - Juliana Fernandes Filgueiras Meireles; Clara Mockdece Neves; Ana Carolina Soares Amaral; Fabiane Frota da Rocha Morgado; Maria Elisa Caputo Ferreira (Frontiers Media S.A., 2022)
BackgroundDuring pregnancy and the postpartum period, women experience tremendous biopsychosocial changes in a short period of time. Poor body appreciation, depressive symptoms, and low self-esteem during the perinatal period may cause negative consequences for both the mother and the infant's physiological and psychological health. The aim of this study was to analyze the differences in body appreciation, depressive symptoms, and self-esteem between the three gestational trimesters and the postpartum period.MethodsParticipants (N = 1,423 pregnant and postpartum Brazilian women), aged between 18 and 42 years old (M = 29.22; SD = ±5.72), answered questionnaires on body appreciation, depressive symptoms, and self-esteem. BMI was self-reported. Descriptive and nonparametric covariance analysis were performed, comparing women who were in the first, second, and third trimesters and the postpartum period.ResultsBody appreciation was significantly higher among women in the third trimester compared to those in the first and second trimester. However, it was lower for women in all three gestational trimesters than for those in the postpartum. There was no difference in self-esteem during pregnancy, but it was significantly lower in the postpartum group. Similarly, depressive symptoms did not vary through pregnant groups but it was significantly higher in the postpartum group.ConclusionsThe results showed that the postpartum period can be a difficult experience for women. They presented poor body appreciation and lower self-esteem and higher depressive symptoms compared to the pregnancy period. Therefore, it is necessary for public health policies to support women in this period, preserving their mental health and making this experience more positive.